Electrical Spinal Stimulation, and Imagining of Lower Limb Movements to Modulate Brain-Spinal Connectomes That Control Locomotor-Like Behavior - Gerasimenko, Yury; Sayenko, Dimitry; Gad, Parag; Kozesnik, Justin; Moshonkina, Tatiana; Grishin, Aleksandr; Pukhov, Aleksandr; Moiseev, Sergey; Gorodnichev, Ruslan; Selionov, Victor; Kozlovskaya, Inessa; Edgerton, V. Reggie (Frontiers in Physiology, 2018)
Neuronal control of stepping movement is based on integration between brain and spinal neuronal networks and sensory signals derived from the limbs. Recently we have demonstrated that the patients categorized as motor complete were able to recovery voluntary control of movement using electrical spinal stimulation and sensory-motor training. It means that these networks have the ability to reorganize to rather dramatic functional levels when driven by activity dependent mechanisms. The mechanisms underlying the emergence of novel brain-spinal network connectomes have a huge clinical impact, and has become an area of very high scientific interest. In the present study we hypothesized that brain-spinal network connectomes can be modulated by descending cortical inputs via imagining stepping and spinal stimulation. The studies were performed on 8 non-injured individuals placed in gravity neutral position. The effects of non-invasive electrical spinal stimulation with and without visual imagery stepping on stepping performance examined. We have provided electrophysiological data showing a modulation of the excitability of locomotor networks that was dependent on the presence or absence of visualizing a stepping pattern displayed by a stick figure mimicking bilateral stepping in the presence of transcutaneous stimulation of the lumbosacral spinal segments (tSCS). We also demonstrated that during voluntary stepping as well as during visual imagery stepping the cortically TMS-evoked motor responses in leg muscles were facilitated whereas spinally tSCS- evoked motor responses were inhibited.